A study on the microstructural evolution and subgrain size dependent constitutive equation of a type of maraging steel in the solid solution treatment process. (2nd April 2021) - Zhu, Y Z; Zhao, T Y; Huang, H; Peng, H; Hu, F W; Yin, S Y
Abstract: 00Cr12Ni9Mo4Cu2 is an ultra- high strength, maraging stainless steel. Optical microscopy, microhardness measurement, scanning electron microscopy (SEM), and transmission electronic microscopy (TEM) were used to quantitatively investigate the effect of the solid solution parameters on the grain size and the secondary phases of the steel. It was found that the grain size increased from 8.5 um to 28 um when the solid solution temperature was increased from 960 °C to 1040 °C. Meanwhile, the strength of the alloy increased from 822 MPa to 1054 MPa. However, when the temperature was increased from 1040 °C to 1100 °C, the grain size rose dramatically to 55 um, and the strength of the alloy decreased from 1054 MPa to 782 MPa. Most of the original carbides were dissolved when the solid solution temperature increased up to 1040 °C. Finally, a constitutive equation based on the evolution of the subgrain size is proposed, clarifying the relationship between the mechanical properties and microstructures.